Fundamentals of a personalized approach at different stages of newly diagnosed glaucoma - S. А. Zubasheva; T. V. Chernyakova; D. A. Baryshnikova; A. V. Kuroyedov (Российский офтальмологический журнал)
The review is focused on the adherence of glaucoma patients to the immediate start of treatment after the condition has been diagnosed. A personalized strategy, which includes the assessment of the patient's clinical and socio-economic status and the use of medications with proven efficacy, contributes to the formation of long-term adherence to therapy. In particular, the strategy combines preventive and diagnostic measures depending on the patient’s individual characteristics and involves their direct participation. Over 250 risk factors are known to reduce a patient’s adherence to treatment, whereas insufficient adherence can itself be considered as a risk factor for glaucoma progression. The asymptomatic course of the disease or the lack of a noticeable effect of drops instilled often cause the regimen to be violated, whilst the long-term therapy requires determination and self-control of the patient. Combined measures to improve the adherence are based on the specific needs of the patients and are consistent with their lifestyle. As a rule, the patients need special instruction, good means of communication with the doctor, simplified treatment regimens, and an adequate interaction with the public health facilities. Importantly, the therapy start depends not only on the level of intraocular pressure, but also on the stage of the glaucomatous process at which it was first diagnosed.